Hubungan Penggunaan Fasilitas Belajar Dan Motivasi Belajar Dengan Hasil Belajar Ekonomi - Jojon Susanto; Sonedi Sonedi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The purpose of this study was to determine whether there was a significant relationship between: (1) the use of learning facilities with results, (2) motivation to learn with learning outcomes, (3) use of learning facilities and motivation to learn with learning outcomes. This research is quantitative descriptive. the number of samples is 104. The sample selection uses the Probability Sampling technique of simple Random Sampling. Data was collected using questionnaire and documentation methods. Test requirements analysis using the Normality test. The results of the study: (1) There is a positive relationship between the use of learning facilities and learning outcomes, analysis: rx1y = 0. 206 and rtable = 0. 195. (2) There is a positive relationship between motivation to learn and learning outcomes, analilis: rx2y = 0. 225 and rtable = 0. 195. (3) There is a shared positive relationship between the use of learning facilities and learning motivation with learning outcomes, analysis: rx1x2y = 0. 298 and rtable = 0. 195. The relationship is included in the low category because based on the calculation of the coefficient of determination the relationship between the use of learning facilities and learning motivation with economic learning outcomes is found at 8. 88%.